ANALISIS TEKNIK POLA PARENTING YANG BAIK UNTUK MEMBATASI ANAK YANG KECANDUAN GADGET - arafah, fitriani (IAIN Parepare, 2024)
The role of parents is very important in guiding children in today's digital era. One of the suggestions could be to choose shows or broadcasts according to their age. Parenting patterns for children and teenagers in the digital era need to be implemented well by parents. The digital era is unavoidable, so parents need to adapt and choose the right parenting style to face digital exposure. And understanding the concept of parenting patterns for children and teenagers in the digital era includes understanding, the role of parents, the concept of child growth and development as well as various preventive measures that can be taken against incidents including gadgets.